Quote:
Originally Posted by Dragonballful23
Here is how you solve. since 9^(x+2)=3^x, you can say 3^(2x+4)=3^x
Now, just like when you factor quadratic equations, take out the 3.
3x+4=x
2x=4
x=2!

You made a small mistake.
9^(x+2) = 3^x
(3^2)^(x+2) = 3^x
3^(2(x+2)) = 3^x
3^(2x+4) = 3^x
Since the base numbers are the same (3) then for the equation to be equal the exponents must be equal.
2x+4 = x
2x  x + 4 = x  x
x + 4 = 0
x + 4  4 = 0  4
x = 4
Let's check our answer.
9^(4 + 2) = 3^(4)
9^(2) = 3^(4)
1/(9^2) = 1/(3^4)
1/81 = 1/81